2017
DOI: 10.1007/s12369-017-0446-3
|View full text |Cite
|
Sign up to set email alerts
|

Affective Touch in Human–Robot Interaction: Conveying Emotion to the Nao Robot

Abstract: Affective touch has a fundamental role in human development, social bonding, and for providing emotional support in interpersonal relationships. We present, what is to our knowledge, the first HRI study of tactile conveyance of both positive and negative emotions (affective touch) on the Nao robot, and based on an experimental set-up from a study of human-human tactile communication. In the present work, participants conveyed eight emotions to a small humanoid robot via touch. We found that female participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(61 citation statements)
references
References 49 publications
4
54
0
Order By: Relevance
“…This was done in order to assess the potential for NAO to decode emotions based on smart textiles, i.e., WAffI imbued with smart sensors. The dataset was previously utilized in [42] but in the current investigation the analysis, both for encoding and decoding of emotions, focuses on whether the NAO was clothed or not (WAffi-On vs. WAffI-Off).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was done in order to assess the potential for NAO to decode emotions based on smart textiles, i.e., WAffI imbued with smart sensors. The dataset was previously utilized in [42] but in the current investigation the analysis, both for encoding and decoding of emotions, focuses on whether the NAO was clothed or not (WAffi-On vs. WAffI-Off).…”
Section: Resultsmentioning
confidence: 99%
“…Gender was balanced across the two conditions (16 males and 16 females for each condition). Potential gender differences identified in the study were investigated elsewhere [42] and are not the focus of the current paper; however, we include gender as an independent variable within our analysis of touch duration so as to discount interaction effects between gender and clothing type variables. Different subjects are used for WAffI-On and WAffI-Off interaction.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The artificial skin sensors generally have a high spatial resolution (1mm − 4mm) but cover only small surfaces ( 2cm). The second type of application is to use artificial skin to cover the surface of a robot to improve motion guidance and environment sensing [5] as a means to increase human likeness, as well as to encourage contact with end-users [3] or to replicate the camouflaging capabilities of natural cephalopods [66,76].…”
Section: Artificial Skinmentioning
confidence: 99%
“…Based on previous results from a human-robot interaction study [4], we selected seven types of touches (stroke, scratch, poke, press, push, squeeze and grab) and used a soft array sensor to classify them. The results from this previous study showed that squeezing, stroking and pressing constituted more than half (59%) of all tactile interaction in the study.…”
Section: Introductionmentioning
confidence: 99%